Bhutan : the unremembered nation, community and livelihood - karma Ura. (Thimphu : ford University Press, 2023)
Human life is set in context by the first topical chapter on Mothers' Houses, which sketches dwelling construction and materials as well as facilities of water, sanitation clothing and bedding. Looking out to the Nest of houses that comprise a village, the next chapter covers authority, courtship and marriage, birth and the journey after death. Turning to livelihoods, the chapter unfurls experiences of cattle herding, together with the dairy products and their exchange, and cattle breeding. That chapter ends with 'belching and emitting' which introduces the theme of sound, upon which chapter five focuses. Sounds of wind and water, of rituals and liturgies, of birds and beasts, archery and song and language are all narrated. Chapter 5 traces conventions of mobility - across snow and Duar passes, and by the routes that criss-crossed Bhutan for trade and seasonal migration. Particular attention is paid to bridges and their sacred significance. The last chapter settles into farm life in different climes: the cultivation of rice and maize, finger millet, buckwheat and barley as these are experienced in community"-- Provided by publisher.
Vol. 1
Includes bibliographical references and index.
Keywords: Birth of mothers' house; family and village